Multivalidation Analysis of the Risk Factors for Ischemic Heart Disease and Cerebral Infarction - Hino, Fumiaki; Ohki, Masami; Tsubokura, Tokuo; Kajiyama, Goro; Tokumo, Hironori; Nomura, Yoko; Hiraoka, Toshihito; Kawamoto, Toshio; Tazuma, Susumu; Horiuchi, Itaru; Okahashi, M.; Kawanishi, Masahiro; et al. (Nihon Rōnen Igakkai zasshi, 1985)
Serum apolipoproteins and various other risk factors for atherosclerosis were analyzed by a multivalidation technique in normal subjects and patients with old myocardial infarction, angina pectoris and cerebral thrombosis in a steady state. By evaluation with discriminant equations derived respectively for discrimination of patients with the above diseases from normal subjects, the accuracies of the risk factors were found high in the following order. (1) Old myocardial infarction: apolipoprotein A-I/apolipoprotein B, apolipoprotein A-I+A-II/apolipoprotein B, apolipoprotein B, atherosclerotic index, LDL cholesterol, cholinesterase/HDL cholesterol, total cholesterol, triglycerides, apolipoprotein A-II, apolipoprotein A-I, HDL cholesterol, cholinesterase, apolipoprotein C-II, apolipoprotein C-III and apolipoprotein E. (2) angina pectoris: apolipoprotein A-I+A-II/apolipoprotein B, apolipoprotein A-I/apolipoprotein B, triglycerides, apolipoprotein A-I, apolipoprotein B, apolipoprotein C-II, total cholesterol, LDL cholesterol, atherosclerotic index, cholinesterase, HDL cholesterol, cholinesterase/HDL cholesterol, apolipoprotein C-III, apolipoprotein A-II and apolipoprotein E. (3) Cerebral thrombosis: apolipoprotein A-I+A-II/apolipoprotein B, apolipoprotein A-I/apolipoprotein B, apolipoprotein A-II, atherosclerotic index, apolipoprotein A-I, apolipoprotein C-II, HDL cholesterol, cholinesterase, triglycerides, cholinesterase/HDL cholesterol, apolipoprotein C-III, LDL cholesterol, apolipoprotein E, apolipoprotein B and total cholesterol. The above indicates that determination of serum apolipoproteins was very useful for discrimination of old myocardial infarction, angina pectoris and cerebral thrombosis from normal subjects and that determination of apolipoprotein B, total cholesterol and LDL cholesterol was useful for discrimination of old myocardial infarction but not for discrimination of cerebral thrombosis from normal subjects. These results suggested that serum lipids and apolipoproteins have different influences in various arteries, though they are the important risk factors for atherosclerosis and that the pathogenesis of atherosclerosis differs between cardiac and cerebral arteries.